INTERNALIZATION OF TAWAZUN VALUES AND ENVIRONMENTAL AWARENESS IN THE CHARACTER DEVELOPMENT OF STUDENTS AT STATE JUNIOR HIGH SCHOOL 2 TENGARAN, SEMARANG REGENCY - Nafingatun; Sri Maryati; Ahmad Faiq Rivaldhi; Ferika Aulia Mawardi; Ardina Maharani; Muhamad Hani Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the internalization of tawazun (balance) values and environmental awareness in character education at a state junior high school in Semarang Regency, Indonesia. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis involving teachers, administrators, and students. The data were analyzed through Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the cultivation of tawazun is achieved through daily religious practices, classroom integration of ethical and balanced values, and teacher role-modeling, which collectively enhance students’ spiritual, social, and academic equilibrium. Environmental awareness is promoted through structured school programs, including greening projects, waste management, and collective cleaning initiatives, fostering responsibility, cooperation, and ecological sensitivity. Supporting factors include a strong school culture and consistent teacher guidance, while inhibiting factors comprise students’ consumerist tendencies, limited supervision, and insufficient program monitoring. This study highlights a holistic model of character education that unites spiritual and ecological dimensions, demonstrating how balance (tawazun) can serve as a guiding principle for ethical and sustainable behavior. The findings provide practical insights for schools seeking to develop morally responsible and environmentally conscious students, emphasizing the importance of community involvement and continuous reinforcement of values.